A novel mixture of diethylene glycol diethylether and non-flammable methyl-nonafluorobutyl ether as a safe electrolyte for lithium ion batteries. Issue 42 (25th September 2015) - Fang, Shaohua; Wang, Guojun; Qu, Long; Luo, Dong; Yang, Li; Hirano, Shin-ichi
Abstract : Graphite/LiFePO4 cells using a safe electrolyte achieved electrochemical performances close to those of the cells using conventional electrolytes. Abstract : A mixture of diethylene glycol diethylether and non-flammable methyl-nonafluorobutyl ether was introduced as a new electrolyte for lithium ion batteries. And a fluoroethylene carbonate additive was used in this electrolyte to improve the compatibility with the graphite anode. The non-flammability and high flash point of this electrolyte indicated its high safety. This electrolyte had low viscosity and its conductivity reached 3.8 mS cm −1 at 25 °C. Graphite/LiFePO4 coin cells with commercial electrodes were utilized to evaluate the performances of the electrolyte. The rate, cycle and low-temperature performances of the graphite/LiFePO4 cells using this electrolyte were close to those of the cells using the conventional electrolytes with and without the fluoroethylene carbonate additive. These results indicated that this kind of safe electrolyte based on non-flammable hydrofluoroethers and solvents with a high flash point has great potential for practical application.